Direct comparison of [18F]MH.MZ and [18F]altanserin for 5‐HT2A receptor imaging with PET. Issue 6 (7th March 2013) - Hansen, Hanne D.; Ettrup, Anders; Herth, Matthias M.; Dyssegaard, Agnete; Ratner, Cecilia; Gillings, Nic; Knudsen, Gitte M.
ABSTRACT Imaging the cerebral serotonin 2A (5‐HT2A) receptors with positron emission tomography (PET) has been carried out in humans with [11C]MDL 100907 and [18F]altanserin. Recently, the MDL 100907 analogue [18F]MH.MZ was developed combining the selectivity profile of MDL 100907 and the favourable radiophysical properties of fluorine‐18. Here, we present a direct comparison of [18F]altanserin and [18F]MH.MZ. 5‐HT2A receptor binding in pig cortex and cerebellum was investigated by autoradiography with [3H]MDL 100907, [18F]MH.MZ, and [18F]altanserin. [18F]MH.MZ and [18F]altanserin were investigated in Danish Landrace pigs by brain PET scanning at baseline and after i.v. administration of blocking doses of ketanserin. Full arterial input function and high performance liquid chromatography (HPLC) analysis allowed for tissue‐compartment kinetic modeling of PET data. In vitro autoradiography showed high binding in cortical regions with both [18F]MH.MZ and [18F]altanserin. Significant 5‐HT2A receptor binding was also found in the pig cerebellum, thus making this region unsuitable as a reference region for in vivo data analysis in this species. The cortical binding of [18F]MH.MZ and [18F]altanserin was blocked by ketanserin supporting that both radioligands bind to 5‐HT2A receptors in the pig brain. In the HPLC analysis of pig plasma, [18F]MH.MZ displayed a fast and reproducible metabolism resulting in hydrophilic radiometabolites only whereas the metabolic profile of [18F]altanserin as expected showed lipophilic radiometabolites. Due to the slow kinetics of [18F]MH.MZ in high‐binding regions in vivo, we suggest that [18F]MH.MZ will be an appropriate tracer for low binding regions where kinetics will be faster, whereas [18F]altanserin is a suitable tracer for high‐binding regions. Synapse, 2013. © 2013 Wiley Periodicals, Inc.